Evaluation Of “Bursa Kerja Khusus” (Bkk) Program With Logic Model - Deviana Ridhani; Triati; Ambiyar; Fahmi Rizal (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the gap between the standards of the BKK program and the actual facts of the implementation of the BKK program at SMK Negeri 1 Lubuk Sikaping. The main program of the BKK is to provide services and information on job vacancies and to distribute and place a workforce of SMK graduates. Evaluation of the BKK program uses a logical model consisting of several components, namely inputs, activities, outputs, and outcomes. This study uses a qualitative approach that produces descriptive data. Methods of data collection by observation, interviews and documentation. The results of this evaluation study are in the form of the percentage absorption of graduates working, entrepreneurship and continuing to tertiary institutions which are still on a medium scale based on data from graduates of SMK Negeri 1 Lubuk Sikapings in the last 2 years. Therefore, there is a quarterly program evaluation so that the BKK management can improve the BKK program and there is a lot of absorption of SMK graduates for work and entrepreneurship.